Brill's Companion to Greek Land Warfare Beyond the Phalanx - Konijnendijk, Roel,; Kucewicz, Cezary,; Lloyd., Matthew, (Brill's Companions to Classical Studies ;, 2021)
After decades of controversy, there is now a growing consensus that Greek warfare was not singular and simple, but complex and multiform. In this volume, emerging and established scholars build on this consensus to explore Greek warfare beyond its traditional focus on hoplites and the phalanx. We expand the chronological limits back into the Iron Age, the geographical limits to the central and eastern Mediterranean, and the operational limits to include cavalry, light-armed troops, and sieges. We also look beyond the battlefield at integral aspects of warfare including religion, the experiences of women, and the recovery of the war dead.